The force of a tsunami on a wave energy converter - O'Brien, Laura; Renzi, Emiliano; Dutykh, Denys; Dias, Frederic; Christodoulides, Paul (My University, 2012)
With an increasing emphasis on renewable energy resources, wave power technology is fast becoming a realistic solution. However, the recent tsunami in Japan was a harsh reminder of the ferocity of the ocean. It is known that tsunamis are nearly undetectable in the open ocean but as the wave approaches the shore its energy is compressed creating large destructive waves. The question posed here is whether a nearshore wave energy converter (WEC) could withstand the force of an incoming tsunami. The analytical 3D model of Renzi and Dias (2012) developed within the framework of a linear theory and applied to an array of fixed plates is used. The time derivative of the velocity potential allows the hydrodynamic force to be calculated.
Keywords: Tsunamis; Hydrodynamics; Ocean wave power